Penguatan Sertifikasi Halal Produk UMKM di Desa Branjang Kecamatan Ungaran Sebagai Upaya Menunjang Kewirausahaan Mandiri - Bayu Wiratama; Wahyono Wahyono; P. Erianto Hasibuan; Irnin Miladdyan Airyq (I-Com: Indonesian Community Journal, 2024)
Halal food has been recognized as a benchmark that serves as an alternative to ensure product safety. In trade, consumed food must have legal guarantees, including, among others, the halal label. Halal certification is necessary to enhance the competitiveness of business actors in expanding their market share both domestically and internationally, as well as to assure that a product fulfills consumer rights. Providing halal certificates is an added value for SMEs' products in Branjang Village. The purpose of this activity is to provide socialization and training for SME business actors in the process of applying for halal certification. This activity implements the Focus Group Discussion (FGD) method during the counseling activity regarding the process of obtaining halal certificates, including the requirements that must be met. This activity is considered highly urgent, given the halal certification regulations mandated for all food and beverage products, including Micro, Small, and Medium Enterprises (MSMEs) products, as stated in Law No. 33 of 2014 concerning halal product assurance